Kambiyo senetlerinde teminat kaydı - Sarıkaya, Merve (My University, 2018)
Ticari hayatta duyulan güven ihtiyacı, borç ilişkisine giren tarafların edimlerinin zamanında ve tam olarak ifa edileceğine dair teminat talep etmelerini gündeme getirmektedir.

The requirement of trust in business, brings about the demand of security between parties that entered a contractual relationship, concerning timely and completely fulfillment of the counter party.
Keywords: bill of exchange; Civil law; kambiyo senedi security; Medeni hukuk; security clause; teminat; teminat kaydı